2021
DOI: 10.1021/acs.jctc.1c00276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Increased Membrane Realism on Conformational Sampling of Proteins

Abstract: The realism and accuracy of lipid bilayer simulations through molecular dynamics (MD) are heavily dependent on the lipid composition. While the field is pushing toward implementing more heterogeneous and realistic membrane compositions, a lack of high-resolution lipidomic data prevents some membrane protein systems from being modeled with the highest level of realism. Given the additional diversity of real-world cellular membranes and protein–lipid interactions, it is still not fully understood how altering me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 136 publications
6
29
0
Order By: Relevance
“…PMm contains the most abundant lipid types from the average human PM . PMp represents membranes of mung bean hypocotyl that have a more complex lipid mixture than previously modeled plant PMs containing up to 10 lipid types. , The lipid composition of PMf is similar to that of the previously modeled yeast PM, although half of sterol molecules is substituted by an inositol-containing SL, mannosyl-inositol-phosphoryl-ceramide (MIPC) based on the work of Hechtberger et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PMm contains the most abundant lipid types from the average human PM . PMp represents membranes of mung bean hypocotyl that have a more complex lipid mixture than previously modeled plant PMs containing up to 10 lipid types. , The lipid composition of PMf is similar to that of the previously modeled yeast PM, although half of sterol molecules is substituted by an inositol-containing SL, mannosyl-inositol-phosphoryl-ceramide (MIPC) based on the work of Hechtberger et al…”
Section: Resultsmentioning
confidence: 99%
“…Computational modeling and simulation of cell membranes give an opportunity to analyze protein behaviors in their natural membrane environment. It has been demonstrated that using realistic membrane complexity is essentia for reproducing the energetics of conformational transitions in membrane proteins …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] MSMs have been recently used to investigate the conformational dynamics associated with membrane transporters. 19,24,[27][28][29][30][31] MSMs were constructed using MSMBuilder 3.6. 32 The simulation data was analyzed using MDTraj 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The predictive power of MD simulations is limited insofar as the realism used to model the system. As efforts have been cast to make the modeling of lipid bilayers and membrane proteins match experiments with improved realism, 286 so too shall efforts surrounding PTM simulation strive to make our biophysical understanding of processes regulating protein function more complete.…”
Section: Outlooks On Ptm Modeling and Simulationsmentioning
confidence: 99%